52. Impaired visual inhibition in migraine with aura. Issue 4 (April 2016) - Tondo, G.; Strigaro, G.; Cerino, A.; Falletta, L.; Matino, E.; Varrasi, C.; Cantello, R.
Abstract : The pathophysiology of migraine with or without aura (MA, MO) is still a matter of debate. We thus studied patients with MA and MO by means of paired-pulse flash-visual evoked potentials (paired F-VEPs). This technique analyses the overall excitability of visual system as detected from the cortical occipital signal. We enrolled 13 adult patients with MO and 13 with MA. Twenty-two normal subjects served as controls. Stimuli were single flashes, intermingled at random to flash pairs at critical interstimulus intervals (ISIs, 16.5–125 ms) with closed and open eyes. The "single" (unconditioned) F-VEP was split into a "main complex" (50–200 ms after the flash) and a "late response" (200–400 ms). As for paired stimulation, the "test" F-VEP emerged from electronic subtraction of the "single" F-VEP to the "paired" F-VEP. In the MA group, the "main complex" of the "test" F-VEP did not show the size reduction (at ISIs 50–62.5 ms) which was typical among the control and MO groups in the "eyes-closed" state. Paired F-VEPs document a defective neural inhibition in the visual system of patients with MA and may warrant future clinical studies, aiming to evaluate its potential role in the pathophysiology and management of MA.